Strategy for Low‐Loss Optical Devices When Using High‐Loss Materials. Issue 9 (17th July 2022) - Wei, Yanxian; Cheng, Junwei; Wang, Yilun; Zhou, Hailong; Dong, Jianji; Huang, Dongmei; Li, Feng; Li, Ming; Wai, Ping Kong Alexander; Zhang, Xinliang
Abstract : Material loss, especially in metal and 2D materials, is the bottleneck for high‐performance integrated optical devices. Here, a novel concept by utilizing the high‐loss materials in a non‐Hermitian system instead of avoiding the loss materials. It is theoretically analyzed how the complex refractive index affects the loss of optical devices based on a two‐waveguide‐coupled non‐Hermitian system. The results reveal that the loss of optical devices can be improved by increasing the loss of materials or the difference in real refractive indexes. It is experimentally verified that a high loss material can be placed close to the optical waveguide without introducing non‐negligible loss to the optical devices, by demonstrating a thermo‐optic phase shifter with a metallic heater placed very close to the silicon waveguide. As a result, the insertion loss is only 0.1 dB for the 100 μm long heater with a gap of 400 nm, and the largest bandwidth for the metallic heater reaches up to 280 kHz. The finding offers a way to realize high‐performance optical devices with high‐loss materials, contributing to the practical applications of strongly absorbing materials based on non‐Hermitian optics. Abstract : A new strategy for low‐loss optical devices when using high‐loss materials. Using the decoupled phenomenon in the optical non‐Hermitian system, material with high loss can be placed closed to the optical waveguide without introduce non‐negligible light absorption. A high‐speed thermo‐optic phase shifter with metallic heater placed closed to the silicon waveguide is demonstrated to verify the theory.